Development and characterisation of a new line width reference material. (9th October 2015) - Dai, Gaoliang; Zhu, Fan; Heidelmann, Markus; Fritz, Georg; Bayer, Thomas; Kalt, Samuel; Fluegge, Jens
Abstract: A new critical dimension (CD, often synonymously used for line width) reference material with improved vertical parallel sidewalls (IVPSs) has been developed and characterised. The sample has a size of 6 mm × 6 mm, consisting of 4 groups of 5 × 5 feature patterns. Each feature pattern has a group of five reference line features with a nominal CD of 50 nm, 70 nm, 90 nm, 110 nm and 130 nm, respectively. Each feature pattern includes a pair of triangular alignment marks, applicable for precisely identifying the target measurement position, e.g. for comparison or calibration between different tools. The geometry of line features has been investigated thoroughly using a high-resolution transmission electron microscope and a CD atomic force microscope (CD-AFM). Their results indicate the high quality of the line features: the top corner radius of <7 nm, vertical sidewall (slope mostly within 90° ± 0.5°) and very small line width variation (LWR down to 0.36 nm). The application of the developed sample for calibrating the scaling factor and effective tip geometry of the CD-AFM are demonstrated. The scaling factor of the CD-AFM is calibrated to be 0.9988, coinciding well with the theoretical value 1 as the tool was calibrated to a traceable metrological atomic force microscope. The effective width of a CDR120-EBD tip is calibrated as 128.32 nm. Finally, a strategy for the non-destructive calibration of the developed sample is introduced, which enables the application of the reference material in practice.